2021
DOI: 10.1038/s41598-021-91768-1
|View full text |Cite
|
Sign up to set email alerts
|

Life-course pathways from childhood socioeconomic status to type 2 diabetes in mid-late Chinese adulthood

Abstract: The relationship between childhood socioeconomic status (SES) and type 2 diabetes (T2D) remains inconclusive, and the pathways and mechanisms driving this relationship have yet to be clarified. This study aimed to examine the pathways linking childhood SES to T2D prevalence in mid-late adulthood in a low- and middle-income country. The incidence of T2D diagnosed in mid-late Chinese adulthood was assessed using self-reports from the Health and Retirement Longitudinal Study (CHARLS). Childhood SES was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
4
0
2
Order By: Relevance
“…We also need to consider more complex processes in the emergence of NCDs. We know that early-life disadvantages such as low family and parental SES, or bad health in infancy and childhood ( Ding et al, 2021 ; McEniry, 2013 ; Ogunsina et al, 2018 ; Zhang et al, 2021 ), have significant impacts on health in adulthood and old age. Participants in our study were aged from 45 to 115, with birth years spanning from 1900 to 1970, and 68% of them were 45–64 years old (born between 1951 and 1970).…”
Section: Discussionmentioning
confidence: 99%
“…We also need to consider more complex processes in the emergence of NCDs. We know that early-life disadvantages such as low family and parental SES, or bad health in infancy and childhood ( Ding et al, 2021 ; McEniry, 2013 ; Ogunsina et al, 2018 ; Zhang et al, 2021 ), have significant impacts on health in adulthood and old age. Participants in our study were aged from 45 to 115, with birth years spanning from 1900 to 1970, and 68% of them were 45–64 years old (born between 1951 and 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Patients may thus find their families to be the most accessible source of social support. Research has demonstrated that flourishing family functioning can enhance patient self-efficacy, increase positive coping strategies, and reduce negative psychological states ( 11 , 12 ). Thus, the family function may be a protective factor for the prognosis of IBD patients, influencing their mental and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the APOE 4 genotype, which is not modifiable, higher education and intellectually and physically active lifestyles are amenable to improvements. Not only do these factors contribute to cognitive reserve but they have also been linked to reduced risk for other major diseases of aging, including hypertension, 3 type 2 diabetes, 4 and stroke, 5 also known as risk factors for the development of dementia. The Lancet Commission on Dementia Prevention, Intervention, and Care estimated that a third of cases of dementia are potentially preventable with interventions aimed to increase childhood education, exercise, socialization, smoking cessation, management of hearing loss, depression, diabetes, hypertension, and obesity.…”
mentioning
confidence: 99%